Makna dan Pemanfaatan Minyak Atsiri Daun Kayu Putih dalam Kehidupan Masyarakat Lokal - Arif Kuntari (KATALIS: Jurnal Penelitian Kimia dan Pendidikan Kimia, 2026)
Cajuput essential oil is a natural resource that plays an important role in the lives of local communities, not only as an economic commodity but also as part of social and cultural constructions. This study aims to critically examine the meanings and utilization of cajuput essential oil in local community life, as well as the dynamics of meaning transformation in the context of modernization and commercialization. This research employs a qualitative approach with a conceptual case study design based on a literature review of relevant academic journals and scholarly sources. The findings indicate that cajuput essential oil is understood as a form of local knowledge transmitted across generations and embedded in traditional health practices, social relations, and environmental management. Its utilization ranges from domestic use to community-based economic activities. However, the increasing dominance of market-oriented logics tends to shift socio-cultural meanings and may generate unequal access and distribution of economic benefits. This study highlights the importance of participatory and community-based approaches to ensure social, cultural, and ecological sustainability.